Analysis Integrated Marketing Communication Reddoorz East Java 1 in Redseller Application - Pramono, Mukhamad Bagas; Poppy Febriana (Jurnal Spektrum Komunikasi, 2023)
The existence of reseller programs in online businesses has a role as an extension of hands or a function in distribution. Part of reseller activity is the promotion of a product or service in return for the commission of each transaction. With the proliferation of reseller programs, RedDoorz Hotel Indonesia captures opportunities and offers an official reseller program to market RedDoorz hotel rooms through the RedSeller application. RedDoorz is a hotel-based startup that specializes in digital technology. Departing from this phenomenon, this study aims to find out the use of the IMC (Integrated Marketing Communication) strategy applied in informing and promoting reseller programs to the public through the RedSeller application. This study includes qualitatively described descriptively. In this study, interviews were collected through open-ended interview methods so that informants could provide answers or respond with their own sentences. Researchers selected two informants who worked as Area Managers and Senior Corporate Sales & Marketing at Red Doorz Hotel Indonesia East Java Area 1. The Research results conclude that all elements of IMC have been implemented and running well, but some elements are considered effective and have not been effectively applied in informing and promoting the RedSeller application reseller program. Direct marketing, sales promotion, advertising, word-of-mouth marketing, and interactive marketing strategies are considered effective. Meanwhile, public relations, personal selling, events, and experience have not been effective.